Plasminogen Activator Inhibitor-1 Is a Marker and a Mediator of Senescence. Issue 8 (August 2017) - Vaughan, Douglas E.; Rai, Rahul; Khan, Sadiya S.; Eren, Mesut; Ghosh, Asish K.
Abstract : PAI-1 (plasminogen activator inhibitor-1) is a member of the evolutionarily conserved serine protease inhibitor family and a potent and rapid-acting inhibitor of both of the mammalian plasminogen activators. Organismal homeostasis requires physiological levels of endogenous PAI-1, and increased PAI-1 production guides the onset and progression of numerous human diseases and contributes to the multimorbidity of aging. Both chronological and stress-induced accelerated aging are associated with cellular senescence and accompanied by marked increases in PAI-1 expression in tissues. Recent studies suggest that PAI-1 is not only a marker but also a key mediator of cellular senescence and organismal aging. Here, we review the significance of PAI-1 as a bonafide marker, as well as a critical mediator, of cellular senescence associated with aging and aging-related pathologies.